2001
DOI: 10.1007/s003950170076
|View full text |Cite
|
Sign up to set email alerts
|

Integrins α v β 3 and α v β 5 mediate VSMC migration and are elevated during neointima formation in the rat aorta

Abstract: Neointima formation involves tissue expression of matrix proteins and growth factors. The role of alphavbeta3, but not alphavbeta5 integrin in vascular cells has been sufficiently investigated. The aim of the present study was to determine and compare the function of alphavbeta3 and alphavbeta5 integrins in rat aortic (RASMC) and human coronary vascular smooth muscle cells (HCSMC) and to characterize their expression accompanying neointima formation in vivo. RASMC and HCSMC express alphavbeta3 and alphavbeta5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Previous studies have shown that the αvβ3 and αvβ5 integrins mediate VSMC migration on vitronectin (Clyman et al, 1992;Kappert et al, 2001;Stawowy et al, 2004). In this regard, we investigated the effects of function-blocking antibodies against αvβ3 and αvβ5 integrins on the adhesion of aortic VSMCs to βig-h3.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that the αvβ3 and αvβ5 integrins mediate VSMC migration on vitronectin (Clyman et al, 1992;Kappert et al, 2001;Stawowy et al, 2004). In this regard, we investigated the effects of function-blocking antibodies against αvβ3 and αvβ5 integrins on the adhesion of aortic VSMCs to βig-h3.…”
Section: Resultsmentioning
confidence: 96%
“…For example, vitronectin has been shown to mediate VSMC adhesion mainly through the αvβ5 integrin but not through the αvβ3 integrin (Clyman et al, 1992;Kappert et al, 2001;Stawowy et al, 2004). Both the αvβ3 and αvβ5 integrins are elevated during neointima formation in injured aorta (Kappert et al, 2001). We showed here that similar to vitronectin, βig-h3 mediates VSMC adhesion and migration through the αvβ5 integrin but not the αvβ3 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…Kappert et al (45) reported that PDGF-directed migration of rat and human SMCs through gelatin-coated membranes involved not only ␣ v ␤ 3 -integrin but also ␣ v ␤ 5 -integrin by experiments using blocking antibodies to these integrins. Moreover, Liu et al (46) showed that integrin-␣ v ␤ 3 is involved in the migration of rat vascular adventitial fibroblasts stimulated by basic fibroblast growth factor but not by PDGF.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the integrins that are poorly expressed in contractile VSMCs, especially a2b1, a5b1 and avb3, become more prominent in non-contractile state 33 and mediate VSMC migration. [34][35][36][37] a2b1 integrin, a collagen receptor, has been implicated in platelet-derived growth factor (PDGF)-induced VSMC migration. 34 It has been reported that stress fiber disassembly by fibroblast growth factor may promote the differential utilization of a2b1 integrin for VSMC motility.…”
Section: Integrin or Integrins?mentioning
confidence: 99%
“…avb3 and avb5 integrins both mediate VSMC migration. 37 Moreover, endothelin1, which is known to enhance contractility, inhibits av expression. 40 Therefore, it appears that av integrin is downregulated in conditions of increased contractile forces.…”
Section: Integrin or Integrins?mentioning
confidence: 99%